Media, monarchy and power - Blain, Neil, 1951- (Intellect European studies series (Unnumbered), 2003)
Is obsession with the Royal Family in Britain a fact of culture or an illusion of media culture? What interest do the European media display in their royal families? Does twenty-first century monarchy remain a political and ideological force - or is it just an economic commodity? Media, Monarchy and Power provides a radical insight into the cultural and political functioning of royalty in five countries. Blain and O'Donnell examine the bonds between monarchies and their 'subjects' or 'citizens', and the relationships between royal families, the media, and nation-states. Numerous case-studies from press and television in Europe and the UK support a theoretical account of the operation of monarchy and royalty in the media. Central to the concerns of Media, Monarchy and Power are the complex relationship between Britain and Europe and the limits of British political modernization.